2010
DOI: 10.1007/s12036-010-0007-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of high and low amplitude wave trains of cosmic ray diurnal variation during solar cycle 23

Abstract: A detailed study has been conducted on the long-term changes in the diurnal variation of cosmic rays in terms of high and low amplitude wave trains event (HAEs/LAEs) during the period 1996-2008 (solar cycle 23), using the neutron monitor data from Kiel neutron monitoring station. As such, 17 HAE and 48 LAE cases have been detected and analyzed. These HAEs appear quite dominantly during the declining phase as well as near the maximum of the solar activity cycle 23. In contrast, the low amplitude events (LAEs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The long term vector addition diagram of annual average vectors of first harmonic of diurnal variation it is clearly notice that the annual average diurnal phase is shifting to before hours during the nearly solar activity minima in all the even solar cycles (cycles 20,22). It is observed to move in later hours during the odd solar cycles (21, 23).…”
Section: Figure 3 Shows the Average Diurnal Vectors For The Years 19mentioning
confidence: 97%
See 1 more Smart Citation
“…The long term vector addition diagram of annual average vectors of first harmonic of diurnal variation it is clearly notice that the annual average diurnal phase is shifting to before hours during the nearly solar activity minima in all the even solar cycles (cycles 20,22). It is observed to move in later hours during the odd solar cycles (21, 23).…”
Section: Figure 3 Shows the Average Diurnal Vectors For The Years 19mentioning
confidence: 97%
“…Observed diurnal anisotropy is related to sunspot cycle, which also shown rigidity dependent. Moreover, the amplitude and phase of the diurnal anisotropy changes with period of one or two solar cycles [11][12], [14][15][16][17][18][19][20][21][22]. The time of the maximum diurnal variation shows remarkable and systematic phase shift towards earlier hours compare than normal.…”
Section: Introductionmentioning
confidence: 99%
“…The authors attributed this to convective removal of cosmic rays produced by the higher-speed solar wind streams associated with the larger CH. Singh et al (2010) reported that HSSs did not play any significant role in causing high-and lowamplitude wave train events and the phase did not shift to earlier hours, but the DA decreased during the solar activity minima in 2008. Variations in GCR intensity and anisotropy have also been analyzed in terms of a 27 day periodicity, which provides a statistical description of the effects of HSSs and CIRs.…”
Section: Introductionmentioning
confidence: 97%